Pipeline slug flow dynamic load characterization - Reda, A.; Forbes, G.; Sultan, I.; Howard, Ian (American Society of Mechanical Engineers, 2019)
Flow of gas in pipelines is subject to thermodynamic conditions which produces twophase bulks (i.e., slugs) within the axial pipeline flow. These moving slugs apply a moving load on the free spanning pipe sections, which consequently undergo variable bending stresses, and flexural deflections. Both the maximum pipeline stress and deflection due to the slug flow loads need to be understood in the design of pipeline spans. However, calculation of a moving mass on a free spanning pipeline is not trivial and the required mathematical model is burdensome for general pipeline design engineering. The work in this paper is intended to investigate the conditions under which simplified analysis would produce a safe pipeline design which can be used by practicing pipeline design engineers. The simulated finite element models presented here prove that replacing the moving mass of the slug by a moving force will produce adequately accurate results at low speeds where the mass of the slug is much smaller than the mass of the pipe section. This result is significant, as the assumption of point load simplifies the analysis to a considerable extent. Since most applications fall within the speed and mass ratio which justify employing this simplified analysis, the work presented here offers a powerful design tool to estimate fatigue stresses and lateral deflections without the need of expensive timeconsuming inputs from specialized practitioners.